2018
DOI: 10.3390/ijms19030876
|View full text |Cite
|
Sign up to set email alerts
|

Within the Brain: The Renin Angiotensin System

Abstract: For many years, modulators of the renin angiotensin system (RAS) have been trusted by clinicians for the control of essential hypertension. It was recently demonstrated that these modulators have other pleiotropic properties independent of their hypotensive effects, such as enhancement of cognition. Within the brain, different components of the RAS have been extensively studied in the context of neuroprotection and cognition. Interestingly, a crosstalk between the RAS and other systems such as cholinergic, dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
228
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(235 citation statements)
references
References 143 publications
(297 reference statements)
4
228
0
3
Order By: Relevance
“…Although few others with no particular group have also been reported, including mesencephalic astrocyte-derived neurotrophic factor and cerebral dopamine neurotrophic factor (Lindahl et al, 2017). Because a modulatory connection exists between NFs and brain RAS, several studies have suggested the use of brain angiotensin peptides as potential novel compounds to modulate brain functions such as in improving cognition (Jackson et al, 2018). The neurotrophins are made up of five classes, including nerve growth factor, brain-derived neurotrophic factor (BDNF) and neurotrophin-3, 4, 6 (NT-3, -4, -6) (Skaper 2018).…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…Although few others with no particular group have also been reported, including mesencephalic astrocyte-derived neurotrophic factor and cerebral dopamine neurotrophic factor (Lindahl et al, 2017). Because a modulatory connection exists between NFs and brain RAS, several studies have suggested the use of brain angiotensin peptides as potential novel compounds to modulate brain functions such as in improving cognition (Jackson et al, 2018). The neurotrophins are made up of five classes, including nerve growth factor, brain-derived neurotrophic factor (BDNF) and neurotrophin-3, 4, 6 (NT-3, -4, -6) (Skaper 2018).…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…ACE and ENPEP are central enzymes in the RAS, catalysing the conversion of angiotensin I to angiotensin II, and angiotensin II to angiotensin III, respectively. Angiotensin II and III have various effects, mediated primarily through angiotensin receptor I (ATR1) (Jackson et al, 2018), such as the induction of pro-survival signalling, via NF-KB mediated anti-apoptotic molecules, or through PI3K-Akt mediated suppression of caspases (George et al, 2010), the induction of cellular proliferation (Clark et al, 2011; Perdomo-Pantoja et al, 2018) and loss of blood brain EC barrier properties (Biancardi and Stern, 2016). More high grade astrocytoma tumour cells express ATR1, compared to lower grade, and expression is associated with cell proliferation, vascularisation and shorter survival (Arrieta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Renal juxtaglomerular cells constitute the most important source of circulating renin (Persson ) but renin has a low concentration in the brain (Grobe et al . ; Jackson et al ). However, within neurons and astrocytes, an intracellular and secreted prorenin molecule has been identified (Grobe et al .…”
Section: General Mechanisms Of Cns Pericyte Damage In Peripheral Disementioning
confidence: 97%
“…The renin-angiotensin system (in which the enzyme renin cleaves angiotensinogen into angiotensin I, which is then converted into angiotensin II by angiotensin-converting enzyme (ACE) (Jackson et al 2018)), has a key role in the pathophysiology of hypertension, kidney diseases and diabetes (Chawla et al 2010;Stiefel et al 2011;Santos et al 2012). It also regulates contractility in pericytes (Kawamura et al 2004), and expression of NADPH oxidases (Nox) of which Nox4 is expressed in pericytes (Manea et al 2005;Kuroda et al 2014 ; Fig.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
See 1 more Smart Citation